Climate warming over the past half century has led to thermal degradation of permafrost on the Qinghai–Tibet Plateau - Ran, Youhua; Li, Xin; Cheng, Guodong (The Cryosphere, 2018)
Air temperature increases thermally degrade permafrost, which has widespread impacts on engineering design, resource development, and environmental protection in cold regions. This study evaluates the potential thermal degradation of permafrost over the Qinghai–Tibet Plateau (QTP) from the 1960s to the 2000s using estimated decadal mean annual air temperatures (MAATs) by integrating remote-sensing-based estimates of mean annual land surface temperatures (MASTs), leaf area index (LAI) and fractional snow cover values, and decadal mean MAAT date from 152 weather stations with a geographically weighted regression (GWR). The results reflect a continuous rise of approximately 0.04 ∘C a−1 in the decadal mean MAAT values over the past half century. A thermal-condition classification matrix is used to convert modelled MAATs to permafrost thermal type. Results show that the climate warming has led to a thermal degradation of permafrost in the past half century. The total area of thermally degraded permafrost is approximately 153.76×104 km2, which corresponds to 88 % of the permafrost area in the 1960s. The thermal condition of 75.2 % of the very cold permafrost, 89.6 % of the cold permafrost, 90.3 % of the cool permafrost, 92.3 % of the warm permafrost, and 32.8 % of the very warm permafrost has been degraded to lower levels of thermal condition. Approximately 49.4 % of the very warm permafrost and 96 % of the likely thawing permafrost has degraded to seasonally frozen ground. The mean elevations of the very cold, cold, cool, warm, very warm, and likely thawing permafrost areas increased by 88, 97, 155, 185, 161, and 250 m, respectively. The degradation mainly occurred from the 1960s to the 1970s and from the 1990s to the 2000s. This degradation may lead to increased risks to infrastructure, reductions in ecosystem resilience, increased flood risks, and positive climate feedback effects. It therefore affects the well-being of millions of people and sustainable development at the Third Pole.